Addressing Gender-Based Violence in the Latin American and Caribbean Region : A Critical Review of Interventions - Morrison, Andrew (World Bank, Washington, D.C., 2013)
The authors present an overview of gender-based violence (GBV) in Latin America, with special emphasis on good practice interventions to prevent GBV or offer services to its survivors or perpetrators. Intimate partner violence and sexual coercion are the most common forms of GBV, and these are the types of GBV that they analyze. GBV has serious consequences for women's health and well-being, ranging from fatal outcomes, such as homicide, suicide, and AIDS-related deaths, to nonfatal outcomes, such as physical injuries, chronic pain syndrome, gastrointestinal disorders, complications during pregnancy, miscarriage, and low birth-weight of children. GBV also poses significant costs for the economies of developing countries, including lower worker productivity and incomes, and lower rates of accumulation of human and social capital. The authors examine good practice approaches in justice, health, education, and multisectoral approaches. In each sector, they identify good practices for: (1) law and policies; (2) institutional reforms; (3) community-level interventions; and (4) individual behavior change strategies.